Association of Spastic Paraplegia and Short Stature in Patients of Autosomal Recessive Intellectual Disability - Jamshed Khan, Muhammad Hanif, Nayyer Uz Zaman, Dost Muhammad Khan, Muhammad Waqar, Usmanullah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Intellectual Disability “ID” is a genetic disorder, which lead to arrested or incomplete development of the brain. It is the limitation of cognitive skills impairment and decline ability of a person in learning process. ID is the most common health problem in worldwide. These patients have decline intellectual functions and at least limitation in their two or more adoptive skills such as reading, writing abilities, social interactions, Behavioral habits, self-care, communication ability etc. The time period for the diagnosis of ID is the onset of disease before the eighteen years of age. Spastic Paraplegia and short stature is a general terminology using for a group of an uncommon inherited diseases that cause stiffness and weakness in the lower limbs muscles. Gradually its symptoms get worse with the passing of time. It’s also called as familial spastic paraparesis or Strümpell-Lorrain syndrome. SP is classified clinically as “complicated" (syndromic) or "uncomplicated" (nonsyndromic) Spastic Paraplegia. Methods: This study was started in March 2014 to Aug 2015. The criteria for the selection of families were consanguineous families with two or more than two ID patients. The patients were examined, interviewed one by one in friendly atmosphere. Then the blood samples were taken by aseptic method. Blood samples were processed in laboratory. DNA extraction and PCR was done. After that Exome sequencing was used to find the pathogenic variants. The data was analyzed by CATCH. Sanger Sequencing was applied to see the segregation. Results: In ID-family1 the variant of AP4B1 was segregated with the disease phenotype. These ID patients have short stature and Spastic Paraplegia. Mutation in AP4B1 is known to cause intellectual disability. In ID-family2 the variants of WDR62, EML2 and KCNK6 were co-segregated with disease phenotype. But only mutations in WDR62 are known to cause intellectual disability. ID family2 also identified as short stature. In ID-family3 Exome sequencing data reveal no putative variants. Conclusion: The present study was conducted in three consanguineous families for the determination of the responsible genes for intellectual disability. Exome sequencing revealed putative mutations in AP4B1 and WDR62 in two out of three families. In third family we could not locate any putative mutation. Keywords: Intellectual disability ID, Autosomal recessive disorders, Autosomal recessive nonsyndromic ID, Behavioral Abnormality, Segregation, Exome sequencing, Spastic Paraplegia, Short stature.